1997
DOI: 10.1046/j.1365-2141.1997.1833000.x
|View full text |Cite
|
Sign up to set email alerts
|

Macular Haemorrhage in Adult Acute Leukaemia Patients at Presentation and the Risk of Subsequent Intracranial Haemorrhage

Abstract: Summary.Retinal changes are common in adult acute leukaemia patients at presentation, but whether they correlate with the risk of subsequent intracranial haemorrhage is unknown. A 4-year study has been carried out in 82 newly-diagnosed acute leukaemia patients, aged 12-77 years, who were studied prospectively for the presence of intra-retinal haemorrhages (IRH), white-centred haemorrhages (WCH), cotton-wool spots (CWS) and macular haemorrhages (MH). Groups with and without these features were compared for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
0
12
1
Order By: Relevance
“…Karesh et al [5] also found no difference in CR rate between patients with and those without retinopathy. One possibility is that LR may correlate with a higher incidence of fatal complications, and it is known that there is a higher incidence of intracranial hemorrhage within the first 30 days after diagnosis in those with MH [4]. However, even after CR is obtained, the current study shows that LR and IRH still have a significant poor prognostic implication on survival, though the numbers analyzable at that stage are small.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Karesh et al [5] also found no difference in CR rate between patients with and those without retinopathy. One possibility is that LR may correlate with a higher incidence of fatal complications, and it is known that there is a higher incidence of intracranial hemorrhage within the first 30 days after diagnosis in those with MH [4]. However, even after CR is obtained, the current study shows that LR and IRH still have a significant poor prognostic implication on survival, though the numbers analyzable at that stage are small.…”
Section: Discussioncontrasting
confidence: 66%
“…MH was defined as any hemorrhage impinging upon the macula, i.e., an area the size of the optic disc, including the foveola, fovea, parafovea, and perifovea situated two disc diameters temporal to [4]. Leukemic retinopathy (LR) is defined for the purposes of this study as the presence of at least one of these retinal abnormalities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have implicated anemia, thrombocytopenia or leukocytosis in the pathogenesis of leukemic retinopathy [1, 2, 17, 18, 19], but other reports showed no association between fundus oculi findings and laboratory parameters [20, 21, 22, 23, 24]. Our report considers RA in adult AML and is the first to distinguish between two age-related groups of patients when assessing their role as prognostic factor.…”
Section: Discussionmentioning
confidence: 97%
“…A raised haematocrit has been reported as a risk factor in one study [21]. Other factors include blood disorders such as leukaemia [60] and thrombocytopenia [61], as well as the use of thrombolytic, anticoagulant and antiplatelet drugs. This includes ethanol, and a regular intake of three or more units is consistently associated with PICH.…”
Section: Causes and Risk Factorsmentioning
confidence: 99%